Economic dynamic of remittances sent from Spain and the United States to Colombia between 2005-2013: an analysis of cointegration - Gómez, Andrés Mauricio; Ramirez Gutierrez, Zoraida (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The purpose of this paper is to analyze the behavior of remittances from Spain and the United States to Colombia in the last nine years, searching specifically what its long-term determinants are. To achieve it, cointegration analysis validated with an error correction method is implemented. It is found that the series under analysis for both Spain and the United States are cointegrated, i.e. there are stable long-term relationships between remittances, GDP, unemployment and the exchange rate, although the rate of convergence between the short and long term within this ratio is high for the U.S. and slower for Spain.